2020
DOI: 10.1101/2020.04.30.069468
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide mutagenesis identifies factors involved inEnterococcus faecalisvaginal adherence and persistence

Abstract: 21Enterococcus faecalis is a Gram-positive commensal bacterium native to the gastrointestinal tract and an 22 opportunistic pathogen of increasing clinical concern. E. faecalis also colonizes the female reproductive 23 tract and reports suggest vaginal colonization increases following antibiotic treatment or in patients with 24 aerobic vaginitis. Currently, little is known about specific factors that promote E. faecalis vaginal 25 colonization and subsequent infection. We developed a mouse model of E. faecalis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 85 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…It is made The copyright holder for this preprint this version posted February 24, 2021. ; https://doi.org/10.1101/2021.02. 24…”
Section: Og1rf_11456mentioning
confidence: 99%
See 1 more Smart Citation
“…It is made The copyright holder for this preprint this version posted February 24, 2021. ; https://doi.org/10.1101/2021.02. 24…”
Section: Og1rf_11456mentioning
confidence: 99%
“…SmarT TnSeq library #2 is a subset of library #1 and contains 1,948 Tn insertions in intergenic regions or uncharacterized or poorly characterized genes (22,23). These Tn libraries have been used to identify OG1RF genes important for cholic acid resistance, biofilm formation and biofilm-associated antibiotic resistance in microtiter plates, response to phage infection, vaginal colonization, and augmentation of E. coli growth (9,(22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…The second SmarT library consists of 1,946 Tn insertions in poorly characterized genes and intergenic regions and was designed to facilitate genetic screens targeting uncharacterized regions of the genome (13). Both libraries are also available in pooled formats and have been used extensively to identify E. faecalis genes required for biofilm formation, metabolism, response to antibiotics, phage infection, vaginal colonization in a mouse model, and polymicrobial interactions involving E. faecalis (14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…The bacteria‐ and host‐targeting capabilities of the T7SSb have been linked to a role in infectious disease. For example, the bacteria‐targeting T7SSb of E. faecalis was recently shown to be required for the colonization and persistence of this pathogen in a murine vaginal tract infection model (Alhajjar et al., 2020). Other studies have indicated a more direct role in pathogenesis with the T7SSb of S. aureus being implicated in direct targeting of host cells (Burts et al., 2005; Korea et al., 2014).…”
Section: Introductionmentioning
confidence: 99%